Pediatric IBD patients show medication and disease activity dependent changes in NK cell and CD4 memory T cell populations - Pappa, Angeliki; Mührer, Julia; Gast, Patricia; Hebbar Subramanyam, Sudheendra; Ohl, Kim; Muschaweck, Moritz; Wagner, Norbert; Wenzl, Tobias; Tenbrock, Klaus (Frontiers in Pediatrics, 2023)
Objectives: CD4+ memory T cells facilitate long-termed adaptive immune responses while NK cells are predominately rapid effector cells with significant functions for both intestinal homeostasis and inflammation. We wanted to study both populations in health and pediatric inflammatory bowel disease (IBD) and correlate them with disease activity and medication.Methods: We performed flow cytometric analyses of peripheral blood CD4+CD45RO+ memory T cells and CD3-CD16+CD56+ NK cells in 30 patients with IBD and 31 age-matched controls and correlated percentages of subsets with disease activity (PUCAI/PCDAI) and medication.Results: We found a significant reduction of peripheral NK cells in overall IBD patients with both clinical remission and disease activity, which was even more pronounced in patients treated with azathioprine. Otherwise, circulating CD4+ memory T cell populations were significantly enhanced in active IBD compared to controls. Enhancement of memory T cells was particularly found in new onset disease and correlated with disease activity scores.